Neurological Safety of Oxaliplatin in Patients with Uncommon Variants in Charcot-Marie-Tooth Disease Genes - Le-Rademacher, Jennifer G. (J Neurol Sci, 2020)
Oxaliplatin therapy can be complicated by chemotherapy-induced peripheral neuropathy (CIPN). Other neurotoxic chemotherapies have been linked to single nucleotide variants (SNV) in Charcot-Marie-Tooth disease (CMT) genes. Whether oxaliplatin carries increased risks of CIPN due to SNV in CMT-associated genes is unknown. 353 patients receiving oxaliplatin in NCCTG N08CB were serially evaluated for CIPN using a validated patient-reported outcome (PRO) instrument, the CIPN20 questionnaire (sensory scale). 49 canonical CMT-associated genes were analyzed for rare and common SNV by nextgen sequencing. The 157 patients with the highest and lowest susceptibility to CIPN (cases and controls) harbored 270 non-synonymous SNV in CMT-associated genes (coding regions). 143 of these were rare, occurring only once (“singletons”). CIPN cases had 0.84 singletons per patient compared with 0.98 in controls. An imbalance in favor of cases was noted only in few genes including PRX, which was previously highlighted as a candidate CIPN gene in patients receiving paclitaxel. However, the imbalance was only modest (5 singleton SNV in cases and 2 in controls). Therefore, while singleton SNV were common, they did overall not portend an increased risk of CIPN. Furthermore, testing CMT-associated genes using recurrent non-synonymous SNV did not reveal any significant association with CIPN. Genetic analysis of patients from N08CB provides clinical guidance that oxaliplatin chemotherapy decisions should not be altered by the majority of SNV that may be encountered in CMT-associated genes when common genetic tests are performed, such as exome or genome sequencing. Oxaliplatin’s CIPN risk appears unrelated to CMT-associated genes.